Indicators of resilience in socio-ecological production landscapes (SEPLs) - Bergamini, N.; Blasiak, R.; Eyzaguirre, Pablo B.; Ichikawa, Kaoru; Mijatović, Dunja; Nakao, F.; Subramanian, S.M. (United Nations University, 2013)
The following policy report constitutes an important supplement to a set of 20 indicators for resilience in socio-ecological production landscapes (SEPLs) that was developed over the course of joint collaboration between Bioversity International and the United Nations University Institute of Advanced Studies (UNU-IAS). The indicators were disseminated widely in pamphlet form for the first time in March 2012. Subsequently, a need was identified for sharing a more in-depth overview of the considerations that went into creating this list of indicators as well as the outcomes of initial field-testing.